Software engineering trends and techniques in intelligent systems : proceedings of the 6th Computer Science On-line Conference 2017 (CSOC2017).: proceedings of the 6th Computer Science On-line Conference 2017 (CSOC2017). Vol 3 ([2017]) - Unknown
No abstract available